Meditation as a complementary practice in health for hypertensive (Research, Society and Development, 2020)
The Meditation, as a complementary practice, can be useful in hypertension in a way that contributes to the control of stress and can promote positive physiological responses. Objective: to identify the scientific evidence on the practice of meditation in the treatment of hypertensive patients. Methodology: this is an integrative review about meditation as a complementary health practice for hypertension. The search was carried out by consulting scientific articles from March to July 2019 in electronic databases, including articles published in full between the years 2013 and 2019. Results: of the 193 studies initially identified, only five publications make up the review, referring to randomized clinical trials, which points to types of meditation such as transcendental, Zen, based on brain education or reduction of stress and mindfulness, Conclusion: it was observed that meditation brings benefits in aspects of quality of life, in biochemical markers and in cardiovascular parameters.